Design of Wireless Power Transfer SystemDesign of Wireless Power Transfer System - Al-shari, Khadija; Alfarsy, Mohammed; Salem , Saleem; El labbar, Abdelslam (Journal of Pure & Applied Sciences, 2022)
In the recent years of the twenty first century, the world has witnessed a noticed evolvement in wireless techniques, such that wireless phones, wireless electronic devices, wireless communication and wireless power transfer. Wireless power transfer is a modern technique used to transfer an electric energy from a source to a destination that is consumed to the load. Wireless power transfer is an important for many applications like, wirelessly powered home appliances that received the power from a transmitting device wirelessly. For example lighting of bulbs, operating of electric equipment and wireless charging for electric tooth brush and charging mobiles. In the developed countries there is wireless charging of electric vehicles is based on magnetic resonance field as in Japan. Based on this concept , the idea of this paper has been chosen. This paper aims to design a wireless power transfer system. This design has accomplished three tasks: one is to build a Tesla Tower design circuit and measuring the possible efficiency can be obtained. It's got satisfied results to about 70%. The second task is to build a magnetic coupled circuit that is based on the idea of wireless mobile charging technique. During our work, it's studied the power efficiency and its related to the distance between transmitter and receiver, the diameter of the coils and number of turns. To enhance our results, it's suggested to connect and design of these circuits by simulation using Multisim software and get the desired goal.